Pengaruh Pemberian Zat Pengatur Atonik Dengan Konsentrasi Berbeda Terhadap Pertumbuhan Dan Hasil Tanaman Terung: (Solanum Melongena L) - Maya F. Roman; Abdonia W. Finmeta; Nur Aini Bunyani; Aldi Poenomo; Windy Djo Hau; Angry Selan (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2022)
A study has been conducted in the village of Noelbaki research was conducted in August to October 2022 Month in the Village Oebelo District of Central Kupang Kupang regency, with the aim of knowing the effect of growth regulators on the growth, hasildan konsentari most effective plant eggplant. Research using a completely randomized design (CRD), which consists of four fertilizer treatments Atonik namely T0: without treatment (control); T1: 0.5 ml / liter of water; T2:: 0.75 ml / liter of water -; T3:: 1.0 ml / liter of water is repeated 3 times. Anova test results if there is a real effect then continued with Duncan Multiple Test.The results showed that treatment Atonik fertilizer with a dose of 1.0 ml / liter of water provide the best results on plant height number of leaves and number of fruits and fruit number even though the treatment is not significant to the treatment amount of interest and the amount of fruit.